Long-term climate change effects on power performance of wave energy converters: A case study - Mahmoodi, Kumars; Fard, Hossein Rezaie; Böling, Jari (Elsevier BV, 2025)
The power performance of wave energy converters (WECs) is directly related to the characteristics of ocean waves, which are influenced by climate change through variations in wave height, frequency, direction, and storm intensity. This study investigates the impacts of long-term sea state climate variability on the power performance of single-body heaving point absorber WEC arrays through a case study of four geographically diverse regions: the Western Tropical Pacific, Southwest Indian Ocean, North Pacific, and South Atlantic. The trends and evaluation of wave energy availability, along with the power absorption of four WEC array configurations across different temporal and spatial resolutions, are analyzed using the ERA5 European Centre for Medium-Range Weather Forecasts (ECMWF) historical hourly wave condition dataset from 1940 to 2023. The results highlight regional differences in the effects of climate change on wave energy potential and WEC power performance. Statistical methods, including the Mann–Kendall trend test, are employed to quantify trend magnitude and direction. Despite an overall increase in absorbed power due to climate-driven changes in wave patterns, observed trends in CWR and q-factor are not uniformly positive, highlighting the complex influence of wave-structure interactions and inconsistent wave climates. This analysis underscores the importance of understanding both spatial and temporal changes in wave conditions when optimizing WEC array layouts for sustained, efficient energy capture in a changing climate.